Stereo‐ and Regioselective Alkyne Hydrometallation with Gold(III) Hydrides. (4th September 2016) - Pintus, Anna; Rocchigiani, Luca; Fernandez‐Cestau, Julio; Budzelaar, Peter H. M.; Bochmann, Manfred
Abstract: The hydroauration of internal and terminal alkynes by gold(III) hydride complexes [(C^N^C)AuH] was found to be mediated by radicals and proceeds by an unexpected binuclear outer‐sphere mechanism to cleanly form trans ‐insertion products. Radical precursors such as azobisisobutyronitrile lead to a drastic rate enhancement. DFT calculations support the proposed radical mechanism, with very low activation barriers, and rule out mononuclear mechanistic alternatives. These alkyne hydroaurations are highly regio‐ and stereospecific for the formation of Z ‐vinyl isomers, with Z / E ratios of >99:1 in most cases.